Application of The Journalistic Code Of Ethics For Press LPM Dynamics State Islamic University of North Sumatra In News - Matondang, Razkiatul Fitri; Anang Anas Azhar (Dinasti Research, 2024)
This research was conducted to analyze how the application of the journalistic code of ethics for Journalists of the Student Press Institute (LPM) Dinamika UIN SU in the news about the campus. Due to detected violations in applying the journalistic code of ethics in a campus news. This research uses a descriptive qualitative approach with interview and observation techniques. This research was conducted at the secretariat of LPM Dinamika UIN SU which was attended by 6 informants. The results of this study first, LPM Dinamika has implemented a journalistic code of ethics as a reference or guideline in making and publishing news about campus that refers to article 4. However, there are campus journalists who do not fully understand the journalistic code of ethics, especially in article 5. Second, to prove that all campus news is honest and can be accounted for, LPM Dinamika verifies information by keeping an archive of interviews or evidence of events. Third, the challenges faced by LPM Dinamika internally are the lack of understanding of journalists in the application of the journalistic code of ethics and the external challenge of the destruction of the LPM Dinamika secretariat. Fourth, the solution to the challenges faced is that LPM Dinamika provides training on understanding the journalistic code of ethics and processing journalistic language in campus news properly.